Pengaruh Kualitas Kehidupan Kerja terhadap Kepuasan Kerja Karyawan Rumah Sakit Ibu dan Anak X Surabaya - Rinanti Rahayuning Bekti (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
Background: The turnover rate in RSIA X Surabaya increased during the last two months from January to February 2018. Turnover rate in January 2018 was 1.56% and in February 2018 was 2.38%. The increased turn over rate in RSIA X Surabaya was probably due to poor quality of work life that can be influenced to performance satisfaction and causing employee resign from their job.Aim: This research aimed to analyze the influence of quality of work life toward employee job satisfaction in RSIA X Surabaya.Method: It was an analytical study by cross sectional design. The samples were 57 respondents chosen by simple random sampling.Results: The result of this research showed that quality of work life had an influence toward employee job satisfaction in RSIA X Surabaya with significance value equal to 0.024 or <α = 0.05. It showed that employee job satisfaction increases along with the better quality of work life.Conclusion: In conclusion, there was an influence of quality of work life towards employee satisfaction. The hospital should take more attention to the quality of work life for employees in the future so that employees still continue working in the organization.Keywords: employee, job satisfaction, quality of work life